Almost Weakly $(τ_1,τ_2)$-continuous Functions (European Journal of Pure and Applied Mathematics, 2025)
This paper is concerned with the concept of weakly $(τ_1,τ_2)$-continuous functions. Furthermore, several characterizations and some properties of almost weakly $(τ_1,τ_2)$-continuous functions are investigated.
Keywords: $τ_1τ_2$-open set; almost weakly $(τ_1,τ_2)$-continuous function